Stackable pinewood pallet storage keeper (SPPiKe) / Nurrohana Ahmad ... [et al.] - Ahmad, Nurrohana; Hasan, Hazlin; Syed Wahid, Sharifah Norhuda; Awang Kader, Mohd Aidil Riduan; Mohamad, Mastura (2021)
Modern and compact design furniture has gained popularity lately due to the small and limited living or office spaces found in metropolitan and sub-urban areas. The increasing population and high cost of living has made the consumers try to conserve their living space, thus choosing simple yet functional furniture. The rising trend on acceptance of wood-based furniture among the consumers has urged the researchers to produce an innovative multifunction stackable storage keeper from softwood species known as pinewood pallet (Pinus spp). Apart from the issue of material shortage, the use of recycled pinewood pallets supports the notion of environment-friendly furniture as well as in support of the government’s effort towards sustainable development of the furniture industry. In extending the innovative idea, this study was conducted to further investigate consumers’ market acceptance on the upgraded design and use of pinewood pallet in the production of a storage keeper. A total of 213 respondents completed the questionnaires randomly distributed online to the potential buyers who are also the residents of Bandar Jengka, Pahang Darul Makmur. IBM-SPSS version 24 software was used to analyse the survey data including the frequency and descriptive analysis. The results show that the proposed upgraded design and the use of the pinewood pallet have received very good responses from the respondents. On average, they also agreed that the multipurpose stackable storage keeper is suitable to be commercialised. It is hoped that the findings provide further understanding and better picture on the consumers’ acceptance and preferences on wooden pallet furniture, thus providing the booster to encourage commercialisation of wood pallet furniture in the furniture industry.